2011
DOI: 10.22436/jmcs.02.04.06
|View full text |Cite
|
Sign up to set email alerts
|

Using The Fuzzy Ahp Methodology In Customerâs Purchasing Decision-making Process Based On Marketing Mix 4ps

Abstract: In purchasing process, whether in traditional or online, we face the problem of comparison and decisionmaking. Also given the fact that the main criteria which are considered by most customers in purchasing process are marketing mix (4Ps), so we take into consideration these criteria as the main criterion. Moreover, lack of certainty and definability of these criteria in fuzzy form lead us to model customer's purchasing decision-making process by using the fuzzy AHP methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Customers are more likely to purchase products with promotions. Basirat and Ana have verified that promotion influences marketing performance in their research [10,11]. In 2022, Desi demonstrated that promotion has a significant influence on customers' purchasing intention by using a survey and SPSS application [13].…”
Section: Important Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Customers are more likely to purchase products with promotions. Basirat and Ana have verified that promotion influences marketing performance in their research [10,11]. In 2022, Desi demonstrated that promotion has a significant influence on customers' purchasing intention by using a survey and SPSS application [13].…”
Section: Important Resultsmentioning
confidence: 90%
“…It means that a better place can promote customers' purchasing intention. In 2021, Basirat and Desi demonstrated that place promotes customers' purchasing intentions [10,13]. However, Ana has argued in the research that place doesn't influence marketing performance [11].…”
Section: Important Resultsmentioning
confidence: 99%
See 1 more Smart Citation